The inbetweenness of things : materializing mediation and movement between worlds - Basu, Paul (Bloomsbury Academic, an imprint of Bloomsbury Publishing, Plc, 2017)
"We habitually categorize the world in binary logics of 'animate' and 'inanimate', 'natural' and 'supernatural', 'self' and 'other', 'authentic' and 'inauthentic'. The Inbetweenness of Things rejects such Western classificatory traditions -- which tend to categorize objects using bounded notions of period, place and purpose -- and argues instead for a paradigm where objects are not one thing or another but a multiplicity of things at once. Adopting an 'object-centred' approach, with contributions from material culture specialists across various disciplines, the book showcases a series of objects that defy neat classification. In the process, it explores how 'things' mediate and travel between conceptual worlds in diverse cultural, geographic and temporal contexts, and how they embody this mediation and movement in their form. With an impressive range of international authors, each essay grounds explorations of cutting-edge theory in concrete case studies. An innovative, thought-provoking read for students and researchers in anthropology, archaeology, museum studies and art history which will transform the way readers think about objects."--Bloomsbury Publishing